PURCHASE DECISIONS AFFECTED BY SHOP ATMOSPHERE, PRICE AND QUALITY OF SERVICE - Fiderius Ismanto; Nuruddin Mahmud (SEAN Institute, 2022)
This study aims to examine the Effect of Store Atmosphere, Price, and Quality Service To Decision Purchase consumers This sampling technique using nonprobability sampling , with one of the methods used is purposive sampling . Research this data using questionnaire with a sample of 100 respondents. data that obtained then analyzed with program SPSS.Results study this is: (1) Atmosphere Shop influential positive and significant to Purchase Decision . (2) Price has a negative effect on Decision Purchase (3) quality service influential positive and significant to Decision Purchase and (4) in a manner together Atmosphere Shop and Quality Service influential positive and significant to Decision Purchase consumer .